The effects of using contextual clues strategy in improving students vocabulary - Amarjit Kaur Kartar Singh (2019)
This quasi-experimental study aimed to investigate the effects of using contextual cluesstrategy to understand the meaning of words while reading a text among Form 1 students. Thesamples of this study, consisting of70 students, were divided equally into a control (n=35) anda treatment group (n=35). Data were collected through a pre and a post test and analyzed usingthe t-test. The findings showed that there was a significant difference in the mean score of pretestand post-test at p value. The value of t for each group was .584 and -18.602 at a level ofp